A Study on Temperature Variation of the Upper Thermosphere in the High Latitude Through the Analysis of 6300 Å Airglow Data - Jong-Kyun Chung; Yong Ha Kim; Young-In Won; Bang Yong Lee (Journal of Astronomy and Space Sciences, 1997)
The temperature of the upper thermosphere is generally varied with the solar activity, and largely with geomagnetic activity in the high latitude. The data analyzed in this study are acquired at two ground stations, Thule Air Base(76.5 degN, 68.4 degW, ¡ü = 86deg) and Sondre Stromfjord (67.0 degN, 50.9 degW, ¡ü = 74deg), Greenland. Both stations are located in the high latitude not only geographically but also geomagnetically. The terrestrial night glow at 6300 A from atomic oxygen has been observed from the two ground-based Fabry-Perot interferometers, during periods of 1986 - 1991 in Thule Air Base and of 1986 - 1994 in Sondre Stromfjord. Some features noted in this study are as follows: (1) The correlation between the solar activity and the measured thermospheric temperature is highest in the case of 3¡ÂKp¡Â4 in Thule, and increases with tile geomagnetic activity in Sondre Stromfjord. (2) The measured temperatures at Thule is generally higher than those at Sondre Stromfjord, but the latter shows steeper slope with the solar activity. (3) The harmonic analysis shows that the diurnal variation(24 hrs) is the main feature of the daily temperature variation with a temperature peak at about 13 - 14 LT (LT = UT-4). However, the semi-diurnal variation is evident during the period of weak sole. activity. (4) Generally the predicted temperatures from both MSIS86 and VSH models are lower than the measured temperature, and this discrepancy grows as the solar activity increases. Therefore, we urge modelers to develope a new thermospheric model utilizing broader sets of measurements, especially for high solar activity.